A wear-resistant anti-bleeding foldable high-filled calcium carbonate hollow plate and a preparation method thereof

CN122941098APending Publication Date: 2026-10-20HEZHOU GREEN TREE ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610848496.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-12
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]因此,本发明提供了一种耐磨防脱墨可折叠高填充碳酸钙中空板及其制备方法,解决现有高分子复合材料领域面临的共性技术难题

Benefits of technology

[0017]本发明有益效果为:通过构建以碳酸钙颗粒为无机刚性内核,包覆有钛酸酯偶联剂过渡层与聚烯烃弹性体、马来酸酐接枝聚丙烯与超高分子量聚乙烯微粉共同组成的复合改性填料,在实现高比例无机填充保持板材高刚性承重力的同时,其抗疲劳韧性得到了巨大提升。使得板材既能提供强有力的结构支撑,表现出优异的抗发白与抗断裂能力。此外,超高分子量聚乙烯微赋予了板材表面极其优异的物理自润滑特性。有效抵抗了物流周转过程中的高频机械刮擦,解决了传统高填充板材表面结构松散、极易磨损和持续掉粉的缺陷。同时,马来酸酐接枝聚丙烯增强了界面的物理缠结,为印刷油墨提供了密集的物理与化学锚固点。解决了普通聚丙烯中空板表面张力低、印刷极易大面积脱墨的难题,使得板材在各种复杂的温湿度与物理摩擦环境下,均能保持优异的尺寸稳定性、表面完整性以及油墨附着力,拓宽了其在高品质循环包装与高端广告展示领域的应用范围。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of polymer composite materials and discloses a wear-resistant, ink-resistant, foldable, highly filled calcium carbonate hollow board and its preparation method. The invention provides a wear-resistant, ink-resistant, foldable, highly filled calcium carbonate hollow board and its preparation method, comprising the following steps: taking 140-160 parts of calcium carbonate filler for thermal activation treatment; maintaining the conditions of thermal activation treatment, adding 2-4 parts of titanate coupling agent for chemical anchoring reaction; subsequently adding 14-16 parts of ultra-high molecular weight polyethylene micropowder, 8-12 parts by weight of maleic anhydride-grafted polypropylene as a macromolecular compatibilizer, and 20-40 parts of polyolefin elastomer for physical coating; forming a composite modified filler, which, while maintaining high rigidity and load-bearing capacity of the board through a high proportion of inorganic filling, significantly improves its fatigue toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer composite materials, and more specifically, to a wear-resistant, ink-resistant, foldable, highly filled calcium carbonate hollow board and its preparation method. Background Technology

[0002] With the development of industries such as logistics packaging and advertising displays, polypropylene hollow boards are widely used due to their advantages such as light weight and moisture resistance. To reduce production costs and improve load-bearing rigidity, the industry commonly fills polypropylene with large amounts of inexpensive calcium carbonate. However, in the pursuit of high filler content to reduce costs, traditional hollow boards face serious technical defects.

[0003] Highly polar calcium carbonate is naturally incompatible with the non-polar polypropylene matrix. Under high filler conditions, inorganic particles are prone to agglomeration and the formation of stress concentration points. When the sheet material needs to be pressed or repeatedly folded during packaging, the weak interface cannot dissipate stress, causing the sheet material to exhibit fatal hard and brittle properties. The folded areas are prone to whitening or even direct brittle fracture, completely losing the necessary fatigue folding life.

[0004] Secondly, the large amount of inorganic powder damages the polymer network on the surface of the resin matrix, resulting in a loose surface structure and a sharp drop in wear resistance. During logistics and handling, the surface is easily damaged and continuously sheds powder, affecting not only appearance but also causing dust pollution inside the packaging. Polypropylene is a non-polar, inert material; the disordered exposure of large amounts of untreated calcium carbonate further reduces the wettability and polarity of the board surface. Ordinary printing inks cannot form effective physical or chemical anchoring on the board surface, leading to large-scale ink detachment and lettering loss with slight friction or environmental changes. These technical bottlenecks—such as non-foldability, easy wear and powdering, and ink detachment—severely restrict the high-quality application of high-filled hollow boards. Summary of the Invention

[0005] In view of the aforementioned existing problems, the present invention is proposed.

[0006] Therefore, this invention provides a wear-resistant, ink-resistant, foldable, highly filled calcium carbonate hollow board and its preparation method, solving a common technical problem faced in the field of existing polymer composite materials.

[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution: This invention provides a wear-resistant, ink-resistant, foldable, highly filled calcium carbonate hollow board and its preparation method, comprising the following steps: S1, by weight, 140-160 parts of calcium carbonate filler are subjected to thermal activation treatment; while maintaining the conditions of thermal activation treatment, 2-4 parts of titanate coupling agent are added to carry out chemical anchoring reaction; subsequently, 14-16 parts of ultra-high molecular weight polyethylene micro powder, 8-12 parts by weight of maleic anhydride-grafted polypropylene as macromolecular compatibilizer and 20-40 parts of polyolefin elastomer are added for physical coating; thus forming a composite modified filler; S2 The composite modified filler and 90-110 parts of copolymer polypropylene resin are added to a mixer at 250-350 rpm for premixing before melt blending. Then, in-situ reactive extrusion granulation is carried out at 350-450 rpm by setting a gradient reaction temperature to obtain composite material particles. S3 extrudes the composite material particles through an extruder by setting a gradient molding temperature to obtain the copolymer polypropylene hollow board.

[0008] As a preferred embodiment of the wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method described in this invention, wherein: the amount of calcium carbonate added in step S1 is 150 parts, the amount of titanate coupling agent added is 3 parts, the amount of ultra-high molecular weight polyethylene micro powder added is 15 parts, the amount of maleic anhydride graft compatibilizer is 10 parts, and the amount of polyolefin elastomer added is 30 parts. The mass ratio of maleic anhydride graft compatibilizer to wear-resistant ultra-high molecular weight polyethylene micro powder is 1:1.4-1.6.

[0009] In a preferred embodiment of the wear-resistant, ink-resistant, foldable, highly filled calcium carbonate hollow board and its preparation method described in this invention, the copolymer polypropylene resin in step S2 is 100 parts, the screw speed is 300 rpm, and the twin-screw extruder speed is 400 rpm.

[0010] As a preferred embodiment of the wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method described in this invention, the gradient reaction temperature in step S2 is divided into a melting zone of 170℃-185℃, a reaction zone of 185℃-210℃, and a pressure-building zone of 190℃-200℃.

[0011] In step S3, the gradient molding temperature is 200℃-220℃ and 215℃ from the extrusion end to the molding end.

[0012] As a preferred embodiment of the wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method described in this invention, the temperature of the melting zone is 175°C, the temperature of the reaction zone is 200°C, and the temperature of the pressure-building zone is 190°C.

[0013] As a preferred embodiment of the wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method described in this invention, the gradient molding temperature is 210℃ and 190℃ from the extrusion end to the molding end.

[0014] As a preferred embodiment of the wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method described in this invention, the mass ratio of the maleic anhydride graft compatibilizer to the wear-resistant ultra-high molecular weight polyethylene micro powder is 2:3.

[0015] As a preferred embodiment of the wear-resistant, ink-resistant, foldable, highly filled calcium carbonate hollow board and its preparation method described in this invention, wherein: the parameters of the thermal activation treatment in step S1 are: stirring continuously at 110-115℃ for 15-20 minutes at a speed of 2000-3000 rpm.

[0016] As a preferred embodiment of the wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method described in this invention, the hollow board is uniformly distributed inside with calcium carbonate particles as an inorganic rigid core, and its outer side is tightly wrapped with a titanate coupling agent transition layer and a composite modified filler composed of a composite polymer shell made of polyolefin elastomer, maleic anhydride grafted polypropylene and ultra-high molecular weight polyethylene micro powder. The hydrophilic group at one end of the titanate coupling agent undergoes a chemical anchoring reaction with the hydroxyl groups on the surface of calcium carbonate, while the lipophilic group at the other end is connected to the outer polymer, forming a chemical bond bridging network that penetrates the inorganic rigid filler and the organic polymer layer. The polyolefin elastomer and maleic anhydride-grafted polypropylene form a highly elastic buffer intermediate layer through physical coating and interfacial compatibilization. The ultra-high molecular weight polyethylene micropowder is firmly embedded in this compatible transition network, giving the material extremely excellent physical self-lubricating and friction-resistant properties.

[0017] The beneficial effects of this invention are as follows: By constructing a composite modified filler consisting of calcium carbonate particles as an inorganic rigid core, coated with a titanate coupling agent transition layer and polyolefin elastomer, maleic anhydride-grafted polypropylene, and ultra-high molecular weight polyethylene micropowder, the high rigidity and load-bearing capacity of the board are maintained by a high proportion of inorganic filler, while its fatigue toughness is greatly improved. This allows the board to provide strong structural support and exhibit excellent resistance to whitening and fracture. In addition, the ultra-high molecular weight polyethylene micropowder endows the board surface with extremely excellent physical self-lubricating properties. It effectively resists high-frequency mechanical scratching during logistics and turnover, solving the defects of traditional high-filler boards such as loose surface structure, easy wear, and continuous powdering. At the same time, maleic anhydride-grafted polypropylene enhances the physical entanglement of the interface, providing dense physical and chemical anchoring points for printing inks. This invention solves the problems of low surface tension and easy large-area ink detachment in ordinary polypropylene hollow boards, enabling the boards to maintain excellent dimensional stability, surface integrity and ink adhesion under various complex temperature, humidity and physical friction environments, thus broadening their application scope in high-quality recyclable packaging and high-end advertising display fields. Attached Figure Description

[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 The diagram shows the optimized ratio of calcium carbonate addition.

[0020] Figure 2 The diagram shows the optimized ratio of macromolecular compatibilizer and wear-resistant surface modifier.

[0021] Figure 3 Optimized ratio diagram for the amount of polyolefin elastomer (POE) used as a toughening material.

[0022] Figure 4 This is a diagram showing the optimized dosage ratio of titanate coupling agent.

[0023] Figure 5 This is a speed optimization diagram for the premixing mixer before melt blending.

[0024] Figure 6 This is a diagram showing the optimal speed for a twin-screw extruder.

[0025] Figure 7 This is a temperature optimization diagram of the melt zone in the barrel temperature profile of a twin-screw extruder.

[0026] Figure 8 This is a temperature optimization diagram of the reaction zone in the barrel temperature profile of a twin-screw extruder.

[0027] Figure 9 An optimized temperature profile of the pressure zone in the barrel of a twin-screw extruder.

[0028] Figure 10 This is a diagram showing the optimized temperature for extrusion molding of hollow boards.

[0029] Figure 11 This is a temperature optimization diagram for the extrusion molding die of hollow board.

[0030] Figure 12 A process flow diagram of a wear-resistant, ink-resistant, foldable, highly filled calcium carbonate hollow board and its preparation method. Detailed Implementation

[0031] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0032] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0033] Secondly, the term "one embodiment" or "example" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the invention. The appearance of an embodiment in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that mutually excludes other embodiments.

[0034] Example 1 This embodiment aims to explore a composite material system for hollow boards that combines high modulus support and high toughness buffering, in order to solve the technical bottlenecks of traditional high-filler thermoplastics in the preparation of hollow boards, such as the brittle fracture of the boards and the difficulty in meeting the requirements of continuous extrusion molding with complex hollow molds. To determine the optimal baseline material combination, this embodiment first conducted a systematic material screening experiment.

[0035] 1.1 Screening and Determination of Basic Polymer Matrix To construct a high-filled calcium carbonate hollow board composite material system that combines high modulus support with high toughness buffering and excellent overall performance, the primary task is to determine the optimal matrix resin to achieve this goal. This phase aims to evaluate the overall performance of different types of thermoplastic resins in balancing the rigidity support and impact toughness of the board (indirectly reflected by macroscopic mechanical properties) and their processing stability and environmental adaptability (evaluated by thermal properties and water absorption rate) when a high proportion of inorganic calcium carbonate is introduced into the system.

[0036] Experimental groups (per 100 parts by weight): A1 Copolymer polypropylene (PP); A2 Linear low-density polyethylene (LLDPE); A3 High-density polyethylene (HDPE); A4 Polystyrene (PS); A5 Polyvinyl chloride (PVC); A6 Acrylonitrile-butadiene-styrene copolymer (ABS); A7 Polyamide 6 (PA6); A8 Polyethylene terephthalate (PET). Subsequently, each group of matrix resins was mixed with an equal amount (150 parts by weight) of pretreated activated calcium carbonate and matching additives, and then extruded and granulated in a standardized manner, and further extruded into standard samples.

[0037] According to ISO 180 standard, the notched impact strength of highly filled composite materials was tested at 23°C using an A-notch design to determine their resistance to brittle fracture under stress concentration, thus screening out resins with better toughness. According to ISO 178 standard, the flexural modulus of the material was measured at 23°C to assess its resistance to bending deformation; this indicator directly reflects the basic stiffness level that hollow boards must possess as packaging structural components. According to ISO 306 standard, the Vicat softening point of each group of samples was determined to assess the material's ability to maintain its physical form under heat, excluding resins that pose a risk of heat deformation in common high-temperature applications. According to ISO 62 standard, the water absorption rate of each group of materials was measured at specified temperature and humidity to assess the sensitivity of the matrix molecular chains to moisture, thereby screening out the best resins that can effectively resist hydrolytic degradation and prevent significant dimensional expansion (warping) and mechanical property degradation in the boards.

[0038] Among them, LLDPE and HDPE have high notched impact strength and good toughness, but their low flexural modulus results in insufficient rigidity of the sheets, making them completely unable to meet the basic stiffness requirements of hollow boards as structural components under load. PS, while possessing excellent rigidity, suffers from extremely low notched impact strength, indicating its extreme fragility and susceptibility to brittle fracture under external forces, failing to meet the notched impact strength requirements for practical applications. PVC has a low Vicat softening point and poor heat resistance, posing a significant risk of heat deformation in many common summer storage applications. ABS exhibits excellent toughness, but its heat resistance is also relatively low, struggling to maintain structural stability at around 105℃. PA6 possesses excellent dry mechanical properties and heat resistance; however, its excessively high water absorption rate leads to significant dimensional expansion and warping of the sheets in normal environments, accompanied by a substantial decline in mechanical properties. PET boasts excellent rigidity, but its high water absorption rate, coupled with its highly sensitive molecular chains to moisture, makes it prone to hydrolytic degradation at high temperatures, resulting in a collapse in overall performance. Overall, PP exhibits balanced characteristics without any obvious shortcomings, thus it was established as the matrix resin.

[0039] 1.2 Screening and Determination of Modified Fillers To construct a copolymer polypropylene composite system that combines high modulus support, excellent folding resistance, and controllable cost, after determining the matrix resin and toughening material, it is essential to find an optimal modified filler that can perfectly integrate into the system. This phase aims to evaluate the overall performance of inorganic powders with different microstructures and physicochemical properties in a highly filled system, considering their impact on sheet weight reduction, compressive strength, folding resistance, and control over processing equipment wear.

[0040] Experimental groups (based on 100 parts by weight of copolymerized polypropylene, 150 parts by weight of inorganic powder, and toughening materials and additives in the aforementioned fixed proportions): B1 Nano-grade lightweight calcium carbonate; B2 Talc powder; B3 Calcined kaolin; B4 Mica powder; B5 Wollastonite powder; B6 Barite powder; B7 Precipitated silica; B8 Diatomaceous earth. Subsequently, each group of inorganic powders was physically blended with the resin matrix and additives in a standardized manner, followed by twin-screw extrusion granulation, and further extruded by single-screw extrusion into hollow plate samples of standard thickness.

[0041] During the testing phase, the finished surface density of each group of sheets was accurately weighed and calculated to assess their lightweight advantages in logistics and transportation. The wear rate of the extrusion equipment screw was tested using a surface profilometer and weighing method to assess the feasibility of equipment maintenance for long-term high-fill production. Based on relevant mechanical standards, the longitudinal compressive yield strength was measured on a universal testing machine to assess the material's rigidity as a packaging component; a 180-degree flexural fatigue life test was conducted on an MIT flexural endurance tester to determine the composite material's resistance to brittle fracture under repeated compressive deformation at the hinge.

[0042] 1.3 Screening Experiments for Toughening Materials To construct a copolymer polypropylene / calcium carbonate high-filled hollow board composite system with both high rigidity support and high toughness buffering, exhibiting excellent comprehensive performance, after determining copolymer polypropylene as the optimal matrix resin and nano-sized lightweight calcium carbonate as the optimal inorganic filler, it is necessary to determine the optimal toughening material to overcome the brittleness defect of the ultimate filling. This stage aims to evaluate the comprehensive performance of different types of elastomers and flexible resins with toughening mechanisms in improving the fracture toughness of the material (indirectly reflected by macroscopic impact mechanical properties) and controlling the dilution of matrix rigidity and the deterioration of processing fluidity (evaluated by changes in mechanical modulus and melt flow rate) when introduced into the determined copolymer polypropylene / calcium carbonate base blend system.

[0043] Experimental groups (basic copolymer polypropylene 100 parts by weight, calcium carbonate 150 parts by weight, toughening material 30 parts by weight): C1 polyolefin elastomer; C2 ethylene-vinyl acetate copolymer; C3 hydrogenated styrene-butadiene block copolymer; C4 linear low-density polyethylene; C5 ethylene propylene diene monomer (EPDM) rubber; C6 styrene-butadiene-styrene block copolymer; C7 methyl methacrylate-butadiene-styrene copolymer; C8 chlorinated polyethylene. Subsequently, the toughening material of each group was blended with copolymer polypropylene, pretreated activated calcium carbonate, and matching additives, then extruded and granulated in a standardized manner, and extruded into standard samples.

[0044] According to ISO 180 standard, the notched impact strength was tested at 23°C using an A-notch design to determine the resistance of highly filled composite materials to brittle fracture under stress concentration. According to ISO 178 standard, the flexural modulus of the material was measured at 23°C to assess its resistance to bending and compressive deformation; this indicator directly reflects the rigidity of the hollow board as a packaging box support. According to ISO 1133 standard, the composite particles prepared in each group were tested to assess whether the introduction of different toughening materials would lead to a severe deterioration of the polymer matrix's processing fluidity and extrusion difficulties. According to ISO 75 standard, the heat distortion temperature was determined using Method A (1.80 MPa standard load, 120°C / h heating rate) to assess the hollow board material's ability to maintain its structural shape under the combined effects of summer storage heat and heavy load stacking.

[0045] Among them, ethylene-vinyl acetate copolymer and linear low-density polyethylene have high melt flow rates and good processing and toughening performance, but their longitudinal compressive yield strength is low, resulting in insufficient rigidity of the sheet material, which cannot meet the basic stiffness requirements of hollow boards as structural components. Hydrogenated styrene-butadiene block copolymer has excellent longitudinal compressive yield strength (rigidity), but its melt flow rate is extremely low, failing to meet the processing fluidity requirements for continuous and stable extrusion molding. EPDM rubber has a low melt flow rate and poor micro-dispersion, posing a risk of rubber phase agglomeration and stress concentration in many common applications. Styrene-butadiene-styrene block copolymer has good initial rigidity, but its notched impact strength (toughness improvement) is also low, and it is susceptible to thermal crosslinking and embrittlement. Chlorinated polyethylene has poor compressive rigidity and extremely low processing fluidity; it is highly sensitive to high extrusion temperatures, and severe thermal degradation at high temperatures leads to the collapse of its overall structure and performance. In summary, polyolefin elastomers exhibit excellent overall performance and demonstrate balanced characteristics without any obvious weaknesses, thus they have been selected as the toughening material for this project.

[0046] 1.4 Screening Experiment of Wear-Resistant and Anti-Ink Stripping Surface Modifiers To construct a copolymer polypropylene / calcium carbonate high-filler hollow board composite system with scratch-resistant surface, long-lasting anti-inking properties, and excellent comprehensive mechanical properties, after determining the matrix resin, toughening material, and filler powder, it is necessary to determine the optimal surface modifier to achieve long-lasting self-lubrication. This stage aims to evaluate the efficiency of different chemical structures and mechanisms of action of wear-resistant and slip-resistant materials in improving the surface friction resistance and wear resistance of the board when introduced into the determined basic high-filler blend system (as well as the overall performance in controlling the long-term stability of surface energy and anti-inking printability).

[0047] Experimental groups (based on 100 parts by weight of basic copolymer polypropylene, 150 parts by weight of calcium carbonate, and 15 parts by weight of surface modifier): D1 Ultra-high molecular weight polyethylene micro powder; D2 Polytetrafluoroethylene micro powder; D3 Silicone powder; D4 Erucamide; D5 Molybdenum disulfide; D6 Glass fiber micro powder; D7 Nano alumina. Subsequently, the surface modifiers in each group were mixed with the aforementioned base materials and supporting additives using a standardized twin-screw extruder for granulation, and then further extruded into standard hollow board samples using a single-screw extruder.

[0048] During the testing phase, in accordance with GB / T3960 standard, the Tiber abrasion tester (1000g load, CS-10 grinding wheel) was used to test the Tiber abrasion amount of each group of samples after 1000 revolutions of rotational friction to quantify the wear resistance of the surface; in accordance with ISO8295 standard, the coefficient of friction of the surface was obtained using a coefficient of friction meter to evaluate the smoothness of the surface; after each group of samples was subjected to standardized corona treatment to an initial surface tension of 44 dynes / cm, it was placed in a constant temperature, humidity and light-proof environment for 30 days. Subsequently, the surface tension was measured again using standard dyne reagent and its surface tension decay rate was calculated to accurately assess whether the modifier had the side effect of microscopic migration and precipitation and damage to the printing substrate.

[0049] Among them, silicone powder and erucamide have low dynamic friction coefficients and good lubricity, but their surface tension decay rate is extremely high, and small molecules undergo severe surface migration and enrichment, resulting in a significant drop in surface energy, which cannot meet the basic surface energy requirements for long-term anti-inking printing on hollow boards. Polytetrafluoroethylene micro powder has excellent rigidity for lubrication and friction reduction, with the lowest Tabe abrasion and dynamic friction coefficient in the field, but its extremely low non-stick surface characteristics indicate that its inherently low surface energy makes it impossible for ink to adhere, failing to meet the hard requirements for subsequent ink adhesion. Nano-alumina has excellent surface hardness, but its friction coefficient is too high, and the excessive hard mating wear leads to significant mutual scratching of the boards during turnover and severe wear of the processing screws. In summary, ultra-high molecular weight polyethylene micro powder has excellent comprehensive performance. Although its abrasion and friction coefficient are not extreme absolute values, it maintains extremely high wear resistance and lubricity while having a low surface tension decay rate, exhibiting balanced characteristics without obvious shortcomings. Therefore, it is established as a wear-resistant and anti-inking surface modifier.

[0050] 1.5 Screening Experiment of Matrix Compatibilizer To construct a copolymer polypropylene / calcium carbonate high-filled hollow board composite system with strong interfacial bonding and excellent comprehensive performance, after determining the matrix resin, filler powder, toughening material, and interfacial coupling agent, it is necessary to determine the optimal surface compatibilizer to achieve compatibility bridging in this system. This stage aims to evaluate the comprehensive performance of different types and grafting ratios of compatibilizers when introduced into the determined basic reaction system, in terms of their efficiency in macromolecular chain entanglement and interfacial bonding, as well as their ability to maintain long-term surface polarity stability and control processing rheology.

[0051] Experimental groups: E1 Blank control group (no compatibilizer added); E2 Ethylene-vinyl acetate copolymer (EVA); E3 Maleic anhydride-grafted polyethylene (MAH-g-PE); E4 Glycidyl methacrylate-grafted polypropylene (GMA-g-PP); E5 Acrylic acid-grafted polypropylene (AA-g-PP); E6 Styrene-maleic anhydride random copolymer (SMA); E7 Maleic anhydride-grafted polystyrene (MAH-g-PS); E8 Maleic anhydride-grafted polypropylene (MAH-g-PP). During the testing phase, the tensile yield strength of the specimens was determined according to GB / T1040 standard to assess the material's resistance to structural deformation and determine its rigidity; the notched impact strength of the simply supported beam was determined according to GB / T1043 standard to determine the resistance of highly filled composite materials to brittle fracture under stress concentration; the melt flow rate (MFR) of the system was tested according to ISO1133 standard to assess the rheological smoothness and processing stability of the material in the extrusion die; and the surface tension of the specimens before and after 30 days of static storage was tested using standard dyne reagent according to GB / T14216 standard, and the surface tension decay rate was calculated to assess the long-term stability of the interface layer's anti-inking printing.

[0052] While ethylene-vinyl acetate copolymer and maleic anhydride-grafted polyethylene exhibit good toughness, their non-propylene macromolecular backbone leads to thermodynamic phase separation from the copolymer polypropylene matrix, resulting in low tensile yield strength and insufficient rigidity, failing to meet the basic stiffness requirements for hollow boards as load-bearing structural components. Styrene-maleic anhydride random copolymer and maleic anhydride-grafted polystyrene demonstrate excellent rigidity, but the presence of numerous rigid benzene rings severely hinders the flexible deformation of the molecular chains, resulting in extremely poor toughness and inadequate fracture resistance. Furthermore, although acrylic acid-grafted polypropylene possesses some compatibility, its oxygen-containing groups are prone to dynamic migration after heat processing, resulting in a high surface tension decay rate and poor long-term stability against ink delamination.

[0053] In comparison, maleic anhydride-grafted polypropylene exhibits superior overall performance. This component achieves the most efficient transfer of rigidity and toughness at the microscopic level, while maintaining moderate extrusion rheology and maximally suppressing the surface decay of polar molecules. It displays balanced characteristics without any obvious weaknesses, thus establishing maleic anhydride-grafted polypropylene (MAH-g-PP) as the optimal surface compatibilizer for this invention.

[0054] 1.6 Screening Experiments for Matrix Coupling Agents To construct a copolymer polypropylene / calcium carbonate high-filled hollow board composite system with strong interfacial bonding and excellent overall performance, after determining the matrix resin, filler powder, and toughening material, it is necessary to determine the optimal interfacial coupling agent to achieve this reaction. This stage aims to evaluate the comprehensive performance of different types of coupling materials when introduced into the determined basic reaction system, including their grafting and interfacial bonding efficiency (indirectly reflected by the enhancement of macroscopic mechanical properties) and their ability to control long-term surface energy stability and heat resistance (evaluated by surface tension decay rate and heat distortion temperature).

[0055] Experimental groups (basic copolymer polypropylene 100 parts by weight, calcium carbonate 150 parts by weight, interfacial coupling agent 3 parts by weight): F1 titanate coupling agent; F2 monoalkoxy fatty acid titanate; F3 coordination titanate; F4 silane coupling agent; F5 stearic acid; F6 aluminum-titanium composite coupling agent; F7 aluminate coupling agent; F8 borate coupling agent. Subsequently, the interfacial coupling agents of each group were mixed with the aforementioned base materials and supporting additives using a standardized twin-screw extruder for granulation, and then further extruded into hollow plate samples of standard thickness using a single-screw extruder.

[0056] During the testing phase, in accordance with GB / T2679.5 standard, the 180-degree flexural fatigue life of the samples was determined using an MIT flexural strength tester to assess the resistance to brittle fracture of the highly filled composite material under stress concentration conditions. In accordance with ISO178 standard, the flexural modulus of the material was measured at 23°C to evaluate its resistance to bending deformation. In accordance with ISO75 standard, the heat distortion temperature was determined using Method A (1.80 MPa standard load, 120°C / h heating rate) to assess the material's ability to maintain its shape under both heat and load. In accordance with GB / T14216 standard, the surface tension of the samples before and after 30 days of static storage was tested using standard dyne reagent, and the surface tension decay rate was calculated to evaluate the long-term stability of the interface layer's anti-inking printing properties.

[0057] Among them, monoalkoxy fatty acid titanates and coordination titanates have high 180-degree flexural fatigue life and good toughness, but their flexural modulus is low and their rigidity is severely insufficient, failing to meet the basic stiffness requirements of hollow plates as structural components. Aluminum-titanium composite coupling agents have excellent toughness, but their heat resistance is also relatively low. Boronate coupling agents have excellent rigidity, but their surface tension decay rate is high, and they are highly sensitive to moisture and storage time, undergoing hydrolytic degradation at high temperatures, leading to performance collapse. Titanate coupling agents have excellent overall performance, exhibiting balanced characteristics without obvious weaknesses, thus establishing them as interfacial coupling agents.

[0058] Example 2 This embodiment aims to further optimize the quantitative proportions of the previously selected preferred components (copolypropylene, calcium carbonate, polyolefin elastomer, ultra-high molecular weight polyethylene micropowder, and titanate coupling agent, MAH-g-PP) through a systematic multidimensional matrix and gradient experimental design. Although the functionality of each individual component has been confirmed, the final performance of the composite material is not a simple summation of the properties of each component, but depends on the competition and synergy between the components at the microscopic interface.

[0059] 2.1 Optimization of the calcium carbonate addition ratio The proportion of calcium carbonate added is a key variable determining the final product's performance and processing feasibility. Insufficient calcium carbonate leads to poor stiffness, easy collapse, and inadequate rigidity in the hollow board, resulting in poor cost reduction. Excessive calcium carbonate, on the other hand, causes a sharp increase in material brittleness and a drastic deterioration in melt flowability, failing to meet the basic requirements for continuous extrusion molding of hollow boards. Therefore, this invention designs a series of gradient experiments, with the total mass of the composite material as 100%, setting the mass percentage of nano-sized calcium carbonate as a single variable ranging from 30% to 70%, and establishing nine gradient experimental groups with a 5% increment.

[0060] By standardizing granulation and slab forming processes, three key performance indicators of the materials under different gradient ratios were tested: longitudinal compressive yield strength, DOP oil absorption value, and screw wear rate of the extrusion equipment. The aim was to accurately determine the optimal filling range that can simultaneously meet the balance of high rigidity, excellent toughness, and stable processability.

[0061] Test results are as follows Figure 1 The results show that by constructing a quadratic function to fit the longitudinal compressive yield strength, DOP oil absorption value, and extrusion equipment screw wear rate, a comprehensive performance that balances high rigidity, high flexural strength, and excellent processability is obtained, with the theoretical optimal fitting point being 48.7%. Considering factors such as the control of batching accuracy in industrial continuous production, the integer ratio closest to the theoretical point is finally selected as the preferred process formulation, i.e., 50%.

[0062] 2.2 Optimization Experiment of Macromolecular Compatibilizer and Wear-Resistant Surface Modifier The ratio of compatibilizer (MAH-g-PP) to abrasion-resistant agent (ultra-high molecular weight polyethylene micro powder) is crucial in determining whether the three core properties of a material—internal toughness, surface abrasion resistance, and printability—can be synergistically unified. The ratio exhibits a typical multi-objective performance constraint: simply increasing the amount of compatibilizer can significantly improve flexural toughness, but it leads to excessively high surface polarity, resulting in a severe decrease in ink adhesion after printing (deterioration of surface tension decay rate); while simply increasing the amount of abrasion-resistant agent can achieve excellent scratch resistance, but it will cause a precipitous drop in the material's flexural life due to the disruption of matrix continuity.

[0063] Based on the total mass of the composite material as 100%, a systematic and multi-level binary ratio optimization experiment was conducted on a copolymer polypropylene system filled with a high proportion of calcium carbonate to optimize the ratio of macromolecular compatibilizer (MAH-g-PP) and wear-resistant surface modifier (ultra-high molecular weight polyethylene micro powder).

[0064] Test Results Figure 2 The results show that the flexural fatigue life (internal toughness) initially increases significantly with increasing compatibilizer dosage, then levels off, but continues to decrease with increasing abrasion-resistant agent dosage. The Taber abrasion loss (surface abrasion resistance) decreases significantly with increasing abrasion-resistant agent dosage (performance improves). The surface tension decay rate (printability) is extremely sensitive to compatibilizer dosage, showing a sharp deterioration trend with increasing dosage.

[0065] When the ratio is within a suitable range (3.50%~5.00% for compatibilizer MAH-g-PP and 3.00%~4.00% for abrasion-resistant polyethylene micro powder), the material's flexural life, Taber abrasion loss, and surface tension decay rate simultaneously reach a balanced range of comprehensive performance. Within this range, the flexural life remains stable above the safe limit of 12,000 cycles, the Taber abrasion loss is suppressed to an excellent range below 15.0 mg, and the most critical surface tension decay rate is strictly controlled within 1.00%. To accurately locate this optimal balance point, the three indicators are normalized and weighted for weighted calculation. The simulated theoretical optimal extreme point of comprehensive performance is: compatibilizer MAH-g-PP: abrasion-resistant polyethylene micro powder = 4.285%: 3.482%. Considering the measurement accuracy of industrial production, the gradient ratio closest to the theoretical point was finally selected as the preferred synergistic process formulation of the present invention, namely, the amount of compatibilizer MAH-g-PP is 4.25% and the amount of ultra-high molecular weight polyethylene micro powder is 3.50%.

[0066] 2.3 Gradient Proportioning Optimization Experiment of Toughening Material Polyolefin Elastomer (POE) The amount of polyolefin elastomer (POE) directly determines the dispersion density of the flexible rubber phase within the composite material and the impact energy dissipation mode. Optimizing the formulation effectively toughens the multiphase rigid matrix network, providing the maximum number of stress absorption centers to resist instantaneous dynamic impacts, thereby maximizing the material's overall mechanical properties. If the amount added is too low, the toughening effect is poor, and the material is prone to brittle fracture under stress; if it is too high, it will cause severe softening of longitudinal compressive rigidity and abnormally high melt viscosity, leading to problems such as the inability to continuously extrude.

[0067] This embodiment sets nine gradients of POE addition from 4.0% to 12.0% in 1.0% increments. Premixing of the elastomer with the remaining core components was carried out in a high-speed mixer at an ambient temperature of 23.0°C to ensure uniform dispersion before melt blending of the composite material. All experimental groups underwent reactive granulation using the same twin-screw extrusion process (constant temperature 230.0°C) and standard test specimens were prepared under the same extrusion molding conditions. Key mechanical and rheological properties of each group of samples were tested.

[0068] Test Results Figure 3The results show that the amount of POE has a significant impact on the overall performance of the material. By constructing quadratic function models for notched impact strength, longitudinal compressive yield strength, and melt flow rate (melt index) with respect to the amount of POE, the variation patterns of each performance index were analyzed. The results show that the theoretical optimal points for achieving the highest toughness, highest rigidity, and best processing rheology do not completely coincide (impact strength shows a trend of initial surge followed by a decline, while compressive strength and melt index show a continuous unidirectional decline). To obtain the optimal comprehensive performance that balances extreme high toughness, high load-bearing rigidity, and excellent processing smoothness, we performed range normalization on the three performance indices and conducted multi-objective weighted fitting analysis. The final calculated optimal fitting point extreme value is 8.95%.

[0069] Considering the control factors of the batching accuracy of the loss-in-weight feeder in industrial continuous production, the value that is closest to the theoretical optimum and is easy to operate is finally selected, that is, the optimal amount of toughening material polyolefin elastomer (POE) is 9.00%.

[0070] 2.4 Optimization of titanate coupling agent dosage ratio The dosage of titanate coupling agents directly determines the quality and mode of interfacial bonding between inorganic fillers and the organic matrix. Systematic formulation optimization achieves the most effective monolayer coating and activation of calcium carbonate surfaces, eliminating powder agglomeration defects and maximizing the material's overall mechanical properties and processing stability. If the dosage is too low, the modification effect is poor, and secondary powder agglomeration is easily triggered; if too high, negative problems such as free plasticization, screw slippage, and a sharp drop in mechanical properties will occur.

[0071] In this embodiment, nine gradients of titanate coupling agent were set, ranging from 0.30% to 1.50% in 0.15% increments. The coupling agent was treated in a high-speed mixer to ensure it had fully reacted with the calcium carbonate filler and completed surface activation before melt blending into the composite material. All experimental groups were granulated using the same twin-screw extrusion process (constant temperature 230.0℃), and standard test specimens were prepared under the same injection molding conditions. Key mechanical and processing rheological properties of each group of samples were tested.

[0072] Test Results Figure 4The results show that the dosage of titanate coupling agent has a significant impact on the overall performance of the material. By constructing quadratic function models for tensile yield strength, elongation at break, and steady-state extruder torque with respect to the dosage of titanate coupling agent, and fitting these models, the variation patterns of each performance index were analyzed. The results indicate that the theoretical optimal points for achieving the highest tensile strength, maximum elongation at break, and the most ideal processing torque do not completely coincide. To obtain the optimal comprehensive performance that balances extremely high interfacial anchoring force, excellent toughness, and stable processing rheology, we normalized the three performance indices and performed a multi-objective weighted fitting analysis. The final calculated theoretical optimal fitting extreme point was 0.88%.

[0073] Considering the control factors of ingredient precision in industrial continuous production, the value that is closest to the theoretical optimum and is easy to operate was finally selected, namely, the optimal dosage of titanate coupling agent is 0.90%.

[0074] Example 3 This embodiment aims to verify the optimal proportions of each component determined in the laboratory pilot test in Example 2 through pilot-scale amplification and systematic optimization of industrial process parameters. Although the theoretical formulation has achieved multi-objective global optimization in the microscopic qualitative and quantitative stages, considering the complex engineering environment in large-scale industrial production, its actual reaction kinetics and dispersion behavior often differ significantly from the static pilot test at the laboratory level. Therefore, it is necessary to conduct dynamic pilot-scale experiments to finely adjust and correct the core process window to ensure that the gradient interface structure can still be achieved efficiently and stably under continuous industrial production conditions, thereby guaranteeing the high reproducibility and consistency of the final blank product performance.

[0075] 3.1 Secondary surface treatment of filler The core starting step of the preparation process is the deep surface activation of nano-sized lightweight calcium carbonate. First, 150 parts by weight of nano-sized lightweight calcium carbonate are placed in a high-speed mixer at 110°C to 115°C for 15 minutes of thermal activation to deeply remove adsorbed free moisture from the powder surface and fully activate surface hydroxyl groups. Then, maintaining the system at high temperature and a high speed of 2500 rpm, 3 parts by weight of titanate coupling agent as a surface coating activator are uniformly sprayed through an atomizing nozzle. Under 25 minutes of vigorous mixing, a complete monomolecular chemical anchoring layer is efficiently constructed on the surface of the calcium carbonate particles, completely transforming the originally hydrophilic inorganic surface into an oleophilic state. Immediately afterward, without cooling, 10 parts by weight of maleic anhydride-grafted polypropylene as a macromolecular compatibilizer, 15 parts by weight of ultra-high molecular weight polyethylene micropowder as a wear-resistant surface modifier, and 30 parts by weight of polyolefin elastomer as a toughening material are added simultaneously, and the stirring speed is further increased to 3000 rpm. Utilizing the residual heat and strong mechanical shear force within the system, the macromolecular compatibilizer and toughening elastomer are softened and fully extended. At the same time, wear-resistant micropowder with excellent self-lubricating properties is firmly embedded and encapsulated in the softened resin phase, forming a uniform, dense, and multi-functional synergistic composite coating film on the surface of coupled and activated calcium carbonate within 20 minutes.

[0076] Finally, a composite modified filler with an inorganic core-coupling agent transition layer-toughening and wear-resistant composite polymer shell structure was obtained, which completely eliminated the secondary agglomeration defect of powder under high filling. It also pre-constructed an excellent flowability, impact-resistant buffer network, surface abrasion resistance and optimal interfacial active substrate for subsequent melt blending with copolymer polypropylene matrix.

[0077] 3.2 Optimization of Premixing Mixer Speed ​​Before Melt Blending Before entering the twin-screw extruder, dry premixing of various materials, including polypropylene granules, high-density modified calcium carbonate powder, and elastomers, is crucial for ensuring uniformity in subsequent melt blending. Under optimized temperature profiles and feeding strategies, seven mixer speed gradients were established from 100 rpm to 700 rpm in 100 rpm increments to prepare premixed composite material samples. A comprehensive study of the impact of speed on three core quantitative indicators—mixing uniformity, segregation degree, and electrostatic effects—aimed to determine a process parameter that optimally balances overall performance and reflects the best possible trade-offs.

[0078] Test results show Figure 5As shown in the test results, the mixing uniformity exhibits a typical U-shaped curve as the mixer speed increases. In the low-speed range, the RSD value is high due to insufficient stirring kinetic energy; as the speed increases, the mixing effect improves rapidly; however, when the speed is too high, centrifugal force-induced segregation leads to poor uniformity. By fitting the data points with a quadratic function, the theoretical optimal value (lowest RSD point) is determined to be located at approximately 290 rpm. The theoretical minimum value of segregation occurs around 200 rpm, indicating that under relatively gentle stirring, the macroscopic stratification of the material is least pronounced. The electrostatic effect shows a monotonically increasing curve. The higher the speed, the more intense the friction and the more severe the electrostatic adsorption phenomenon, which is particularly evident after the speed exceeds 400 rpm, representing a decrease in process stability and raw material loss.

[0079] By fitting and differentiating the data, the theoretically calculated optimal uniformity appears at around 290 rpm. Taking into account the core mixing quality, macroscopic stratification suppression, and process feasibility, and to establish a safety margin for process fluctuations in industrial production, the optimal screw speed of this invention was finally determined to be 300 rpm.

[0080] 3.3 Twin-screw extruder speed optimization As a highly efficient microreactor, the twin-screw extruder can controllably achieve in-situ co-grafting reactions. Screw speed is a key parameter determining reaction kinetics and material microstructure. If the speed is too low, insufficient shear force leads to uneven dispersion of the highly packed filler and inadequate mixing of reactants, severely hindering the grafting reaction. Conversely, if the speed is too high, excessive shear heat and short residence time can easily cause matrix degradation and incomplete grafting, impairing the final properties of the material.

[0081] Under optimized surface treatment and premixing mixer speed strategies, seven screw speed gradients were set from 250 rpm to 550 rpm in 50 rpm increments to prepare composite material samples. The material's ability to absorb impact energy and resist brittle fracture was evaluated by assessing notched impact strength, the interfacial bonding strength between the matrix resin and filler was evaluated by assessing tensile strength, and the degree of polymer degradation was evaluated by assessing melt flow index. These factors combined to form a comprehensive assessment.

[0082] Test results show Figure 6As shown, the tensile strength peaks at 300 rpm and then slowly decreases, indicating that a short residence time is not conducive to the full progress of the interfacial reaction. The melt flow index, as a matrix degradation metric, exhibits a clear increasing curve, remaining at a low level below 450 rpm. Beyond this critical value, it rises sharply due to the rapid accumulation of shear heat, indicating an uncontrolled matrix degradation reaction. The notched impact strength shows a clear single-peak distribution. By fitting a function to the data points and taking the derivative, its theoretical peak value can be determined to be located at approximately 410 rpm.

[0083] Taking into account interface bonding, matrix protection, and final toughness performance, and in order to reserve a safety margin for the accumulation of shear heat during long-term operation in industrial production, we finally determined that the optimal screw speed of this invention is 400 rpm.

[0084] 3.4 Segmented Co-optimization of Temperature Profile in Twin-Screw Extruder Barrel After determining 400 rpm as the optimal screw speed, we further refined the barrel temperature profile in the twin-screw reactive extrusion process. The twin-screw extruder here is not only a device for physical mixing and plasticizing, but also a continuously operating micro-reactor. Its internal temperature field, shear field, and residence time distribution collectively determine the efficiency and direction of the in-situ co-grafting reaction. By optimizing each of the three core temperature zones of the extruder—the feed melting zone, the core reaction zone, and the homogenization and pressure-building zone—we sought a temperature profile that achieves optimal reaction efficiency and the highest material properties.

[0085] The feed melt zone is fundamental to the stable operation of the entire reactive extrusion process. Using the temperature of this zone as a variable, experiments were conducted in 5-degree increments within a range of 155℃-195℃. The aim was to achieve a process balance between extrusion stability and plasticizing efficiency, laying a solid foundation for the entire synergistic optimization process.

[0086] Test Results Figure 7 As shown, through data fitting analysis, the theoretical extreme value of extrusion stability (melt pressure RSD) is located at 175.5℃; the theoretical extreme value of energy consumption per unit output is located at 184.5℃; and the bridging risk index shows a monotonically increasing trend. The optimal points for both extrusion stability and energy consumption per unit output are concentrated between 175℃ and 185℃. In a comprehensive trade-off, ensuring extrusion stability, which is the core of production, is paramount. Therefore, 175℃ is determined as the optimal set temperature point for the melting zone. At this temperature, the optimal balance between bridging risk and extrusion stability is achieved, providing sufficient safety margin for long-term industrial production. Using this optimal point as the center, and combining the overall trend of gradient experiments, the optimal process window for the melting zone is finally determined to be 170℃-185℃.

[0087] Based on the optimized feed melting zone temperature, a fine-grained experiment was conducted in the core reaction zone, using the plateau temperature of this region as a variable, with nine gradients in 5-degree increments within the range of 180-220°C. This stage aimed to maximize grafting efficiency and dispersion while minimizing matrix damage at the optimal reaction temperature, thereby maximizing the material's intrinsic properties. The results were comprehensively evaluated using notched impact strength, grafting ratio, and melt flow index.

[0088] Test Results Figure 8 As shown, through data fitting analysis, the theoretical extreme value of notched impact strength is located at 200.5℃; the theoretical extreme value of grafting ratio appears at 205.8℃; and the theoretical extreme value of melt index is located at 180℃. In comprehensive consideration, priority is given to ensuring the notched impact strength, which is the core performance of this invention. Therefore, 200℃ is determined as the optimal set temperature point for the reaction zone. At 200℃, it almost coincides with the theoretical extreme value of toughness, while its grafting ratio is close to saturation, and the degree of matrix degradation reflected by the melt index is in a controllable, slow-increasing stage. This temperature also provides sufficient safety margin for long-term industrial production, effectively avoiding significant degradation caused by excessively high temperatures. Using this optimal point as the center, the optimal process window for the reaction zone is ultimately determined to be 185℃-210℃.

[0089] Considering that the temperatures in the preceding and following regions are lower than this section, a transition gradient region needs to be set up subsequently. Based on the optimal temperatures optimized in the first two sections, this stage conducted fine-tuning experiments with nine gradients within the range of 175℃-215℃, using the end temperature of this region as a variable. This stage aims to achieve the optimal pressure build-up temperature for best product dimensional accuracy, optimal melt strength, and suitable processing pressure. We comprehensively evaluated wall thickness uniformity, melt strength index, and die pressure to make a comprehensive judgment.

[0090] Test Results Figure 9 As shown, through data fitting analysis, the theoretical extreme value of wall thickness uniformity is located at 190.5℃; the theoretical extreme value of melt strength index is located at 175℃; and the theoretical extreme value of die pressure occurs at the highest temperature of 215℃. In comprehensive consideration, priority is given to ensuring wall thickness uniformity, which directly determines product quality. Therefore, 190℃ is determined as the optimal set temperature point for the pressure build-up zone. This temperature point almost coincides with the theoretical optimal value of wall thickness uniformity. Although the melt strength and die pressure at this temperature are not their respective theoretical extreme values, they are both within an ideal range, ensuring sufficient melt strength to support the hollow structure and preventing collapse, while avoiding the risk of excessive pressure and melt rupture due to excessively low temperatures, thus providing sufficient safety margin for process fluctuations. Using this optimal point as the center, the optimal process window for the pressure build-up zone is ultimately determined to be 190℃-200℃.

[0091] 3.5 Comprehensive Optimization of Temperature and Process Parameters for Hollow Board Extrusion Molding System Before entering the vacuum forming stage, the complete plasticization of the high-filler composite masterbatch within the extruder and its stable flow at the die are crucial for ensuring the dimensional accuracy of the final hollow sheet cross-section and the rigidity of the internal supporting ribs. With optimized screw extrusion speed and feeding strategy, nine extrusion molding temperature gradients were set from 185℃ to 225℃ in 5℃ increments to conduct extrusion molding optimization experiments on the hollow sheets. The effects of extrusion molding temperature on the relative standard deviation of sheet wall thickness, die melt pressure, and melt sag were comprehensively evaluated.

[0092] Test Results Figure 10 As shown, the relative standard deviation of the sheet wall thickness exhibits a typical U-shaped curve with increasing extrusion molding temperature. In the low-temperature region, insufficient plasticization of the high-filler material and poor melt flowability lead to uneven extrusion resistance at the die exit, resulting in a higher relative standard deviation value. As the temperature increases, the plasticization state and melt homogeneity improve rapidly. However, when the temperature is too high, the melt strength of the matrix resin decreases significantly, causing the supporting ribs of the hollow sheet to soften and microscopically collapse at high temperatures before cooling after leaving the die, resulting in worse dimensional uniformity. By fitting the data points with a quadratic function, the theoretical maximum value is determined to be located at approximately 208.5℃ during extrusion molding. The theoretical minimum value of the die head melt pressure occurs near the high-temperature region of 225℃, indicating that the back pressure resistance experienced by the extruder is the least. The melt elongation exhibits a monotonically increasing curve. The higher the extrusion temperature, the weaker the viscoelasticity of the melt, and the more severe the sag and drip phenomenon caused by gravity. This is especially evident when the temperature exceeds 215℃, which represents the loss of molding stability and the risk of serious out-of-tolerance geometric dimensions.

[0093] By fitting and differentiating the data, the theoretically calculated optimal dimensional accuracy (wall thickness uniformity) appears at around 208.5℃. Considering the core cross-sectional forming quality, suppression of sagging and collapse defects, and the stability of the extrusion back pressure load, and to establish sufficient safety margin for thermal inertia hysteresis and temperature control fluctuations in long-term continuous industrial production, the optimal extrusion molding temperature of this invention was ultimately determined to be 210℃. Therefore, 200℃-220℃ is a selectable temperature range.

[0094] After plasticizing at 200℃-220℃, the molten material is smoothly pushed into the mold. At this point, the uniform distribution and extrusion flow of the melt within the mold channel constitute the final thermodynamic defense line determining the stiffness of the reinforcing ribs in the hollow plate and the overall geometric profile stability. Under optimized extrusion plasticizing conditions and melt feed pressure, nine temperature gradients for the hollow plate molding molds were set from 195℃ to 235℃ in 5℃ increments for systematic optimization experiments of the molding mold temperature. The effects of mold temperature on the molding profile distortion rate, die head extrusion back pressure, and die orifice precipitate accumulation rate were comprehensively evaluated.

[0095] Test Results Figure 11 As shown, the molding profile distortion rate exhibits a typical V-shaped curve as the molding die temperature increases. In the low-temperature region, the melt viscosity surges upon cooling within the die channel, resulting in extremely uneven distribution of the high-filler material at the splitter, causing internal stress distortion in the extruded reinforcing ribs and a high distortion rate. As the die temperature increases, melt flowability and wall slippage improve rapidly. However, when the die temperature is too high, the molten material leaving the die orifice completely loses its melt strength due to excessive softening, leading to a sharp deterioration in the distortion rate. By fitting the data points with a quadratic function, the theoretical optimal value is determined to be precisely located at a molding die temperature of approximately 214.2℃. The theoretical minimum of the die head extrusion back pressure occurs near the high-temperature region of 235℃, representing the least resistance experienced inside the die head. The accumulation rate of precipitates at the die orifice exhibits a monotonically increasing curve. The higher the die temperature, the more easily the low molecular weight components in the formulation undergo pyrolysis and precipitate, adhering to the die lip. This is particularly evident above 220℃, severely disrupting continuous production stability. By fitting and differentiating the data, the theoretically calculated optimal cross-sectional shaping quality appears at around 214.2℃. Taking into account the core aspects of extrusion profile shaping accuracy, suppression of die precipitate defects, and stability of extrusion back pressure, and in order to establish sufficient safety margin for temperature control fluctuations of the multi-zone heating rods in the die head during industrial production, the optimal temperature for the hollow plate forming die of this invention was finally determined to be 215℃.

[0096] Example 4 Reference Figure 12 This is the fourth embodiment of the present invention. This embodiment aims to fully demonstrate the determined optimal ratio and process parameters, the entire process of preparing highly filled calcium carbonate hollow boards, and to comprehensively test the performance of the final product. Four comparative examples with missing single-factor variables were set up: Comparative Example 1 was a conventional highly filled group with titanate coupling agent and maleic anhydride-grafted polypropylene removed; Comparative Example 2 was a control group with toughening material polyolefin elastomer removed; Comparative Example 3 was a control group with ultra-high molecular weight polyethylene micropowder removed; and Comparative Example 4 was a control group without polar compatibilizer and without any treatment.

[0097] All test samples were left to stand for 48 hours at 23℃ and 50% relative humidity to fully eliminate internal residual stress. Subsequently, the four core properties of the samples were quantitatively tested strictly according to standard procedures: a universal testing machine was used to apply a compressive load along the extrusion direction at a constant speed of 10 mm / min, and the longitudinal compressive yield strength at the moment of instability and yielding of the reinforcing rib was accurately recorded; using an MIT flexural endurance tester, the ultimate flexural fatigue life at which the pressure line completely fractured was tested under a tension of 1.0 kg and high-frequency reciprocating bending at 135 degrees on both sides; using a Taber abrasion tester, the mass difference of the sample before and after the test was weighed after 1000 revolutions of continuous friction, and the surface Taber abrasion amount was calculated; fourth, after a special ink was scraped onto the surface of the board and completely dried and cured, 100 micro-grids were drawn using a standard cross-cutting knife, and 3M test tape was used to tightly adhere the grids and then quickly peel them off, and the percentage of grid area where the ink fell off or the edges were damaged was accurately calculated.

[0098] The hollow boards prepared using the optimized formulation system and fully optimized process described in this invention exhibit significantly improved macroscopic physical properties compared to conventional high-filler processes. Most notably, the flexural fatigue life is significantly enhanced, resolving the extreme brittleness issue caused by high filler content. Simultaneously, the longitudinal compressive yield strength is also strengthened. Furthermore, this invention demonstrates unparalleled superiority in product appearance quality (durable, wear-resistant, and powder-free surface) and commercial printing adaptability (absolutely resistant to ink smudging).

[0099] In summary, this invention constructs a composite modified filler consisting of calcium carbonate particles as an inorganic rigid core, coated with a titanate coupling agent transition layer, a polyolefin elastomer, maleic anhydride-grafted polypropylene, and ultra-high molecular weight polyethylene micropowder. This achieves a high proportion of inorganic filler to maintain the high rigidity and load-bearing capacity of the board while significantly improving its fatigue toughness. This allows the board to provide strong structural support and exhibit excellent resistance to whitening and fracture. Furthermore, the ultra-high molecular weight polyethylene micropowder imparts excellent physical self-lubricating properties to the board surface, effectively resisting high-frequency mechanical scratches during logistics and handling, and solving the defects of traditional high-filler boards such as loose surface structure, easy wear, and continuous powdering. Simultaneously, maleic anhydride-grafted polypropylene enhances the physical entanglement of the interface, providing dense physical and chemical anchoring points for printing inks. This solves the problem of low surface tension and easy large-area ink stripping in ordinary polypropylene hollow boards, enabling the board to maintain excellent dimensional stability, surface integrity, and ink adhesion under various complex temperature, humidity, and physical friction environments, broadening its application range in high-quality reusable packaging and high-end advertising displays.

[0100] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A wear-resistant, ink-resistant, foldable, highly filled calcium carbonate hollow board and its preparation method, characterized in that... Includes the following steps: S1, by weight, 140-160 parts of calcium carbonate filler are subjected to thermal activation treatment; while maintaining the conditions of thermal activation treatment, 2-4 parts of titanate coupling agent are added to carry out chemical anchoring reaction; subsequently, 14-16 parts of ultra-high molecular weight polyethylene micro powder, 8-12 parts by weight of maleic anhydride-grafted polypropylene as macromolecular compatibilizer and 20-40 parts of polyolefin elastomer are added for physical coating; thus forming a composite modified filler; S2 The composite modified filler and 90-110 parts of copolymer polypropylene resin are added to a mixer at 250-350 rpm for premixing before melt blending. Then, in-situ reactive extrusion granulation is carried out at 350-450 rpm by setting a gradient reaction temperature to obtain composite material particles. S3 extrudes the composite material particles through an extruder by setting a gradient molding temperature to obtain the copolymer polypropylene hollow board.

2. The wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method according to claim 1, characterized in that, In step S1, the amount of calcium carbonate added is 150 parts, the amount of titanate coupling agent added is 3 parts, the amount of ultra-high molecular weight polyethylene micro powder added is 15 parts, the amount of maleic anhydride graft compatibilizer added is 10 parts, and the amount of polyolefin elastomer added is 30 parts. The mass ratio of maleic anhydride graft compatibilizer to wear-resistant ultra-high molecular weight polyethylene micro powder is 1:1.4-1.

6.

3. The wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method according to claim 1, characterized in that, In step S2, the copolymer polypropylene resin is 100 parts, and the screw speed is 300 rpm. The twin-screw extruder speed is 400 rpm.

4. The wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method according to claim 1, characterized in that, In step S2, the gradient reaction temperature is divided into a melting zone of 170℃-185℃, a reaction zone of 185℃-210℃, and a pressure-building zone of 190℃-200℃. In step S3, the gradient molding temperature is 200℃-220℃ and 215℃ from the extrusion end to the molding end.

5. The wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method according to claim 4, characterized in that, The temperature of the melting zone is 175°C, the temperature of the reaction zone is 200°C, and the temperature of the pressure-building zone is 190°C.

6. The wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method according to claim 4, characterized in that, The gradient molding temperature is 210℃ and 190℃ from the extrusion end to the molding end.

7. The wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method according to claim 2, characterized in that, The mass ratio of the maleic anhydride graft compatibilizer to the wear-resistant ultra-high molecular weight polyethylene micro powder is 2:

3.

8. The wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method according to claim 1, characterized in that, The parameters for the thermal activation treatment in step S1 are: stirring continuously at 2000-3000 rpm and 110-115℃ for 15-20 minutes.

9. The wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board and its preparation method according to claim 1, characterized in that, The chemical anchoring reaction in step S1 lasts for 10-20 minutes, and the physical coating process takes 15-25 minutes.

10. A wear-resistant, ink-resistant, foldable, high-filling calcium carbonate hollow board, characterized in that, The hollow plate prepared by any one of claims 1 to 9 contains a composite modified filler uniformly distributed inside, consisting of calcium carbonate particles as the core and coated with a titanate coupling agent, ultra-high molecular weight polyethylene micropowder, polyolefin elastomer, and maleic anhydride graft compatibilizer. The titanate coupling agent undergoes a chemical anchoring reaction with the hydroxyl groups on the surface of calcium carbonate to form a chemical bond bridging network that penetrates the inorganic filler and the organic polymer coating layer. The polyolefin elastomer and maleic anhydride graft compatibilizer form a highly elastic and compatible transition layer that is physically entangled with the copolymer polypropylene matrix through physical coating and compatibilization, and the ultra-high molecular weight polyethylene micropowder is firmly embedded in the transition layer.